A STUDY OF THE FACTORS INFLUENCING THE LOCATION SELECTION DECISIONS OF INFORMATION TECHNOLOGY FIRMS - Paulrajan Rajkumar (Asian Academy of Management Journal, 2013)
A study was conducted to understand the factors influencing the location selection decision making of information technology companies in India. The development of industrial estates has witnessed a phenomenal growth due to the globalisation policy of the government of India. Seven constructs, such as manpower, technology, social, hedonistic, industrial site, economic and governmental factors, and their underlying items play vital role in location selection decisions. A pilot study was conducted to understand the market and frame an effective questionnaire. The survey was conducted with a structured questionnaire among the personnel from information technology organisations, government, and support service organisations. The collected data from the respondents was analysed to reduce it into meaningful factors. The factorised data and the constructs were further analysed with the help of structural equation model. These analyses and path diagram reveal new dimensions in the location decision-making process.